2020
DOI: 10.1002/aenm.202001802
|View full text |Cite
|
Sign up to set email alerts
|

Domain Wall Free Polar Structure Enhanced Photodegradation Activity in Nanoscale Ferroelectric BaxSr1‐xTiO3

Abstract: Ferroelectric materials exhibit anomalous behavior due to the presence of domains and domain walls which are related to the spontaneous polarization inherent in the crystal structure. Control of ferroelectric domains and domain walls has been used to enhance device performances in ultrasound, pyroelectric detectors, and photovoltaic systems with renewed interest in nanostructuring for energy applications. It is also known that ferroelectrics including domain walls can double photocatalytic rate and increase ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 27 publications
(25 reference statements)
1
14
0
Order By: Relevance
“…[22] This unique single-domain-single-grain polycrystalline structure can be used for a mechanistic study of polycrystalline BiFeO 3 film in multifunctional applications without a domain wall contribution. [23] Figure 5a shows the UV-vis spectra of the three thin films with Figure 5b showing the derived Tauc-plots. From the absorption spectra, it can be seen that the BiFeO 3 thin films annealed in different atmospheres have a very close light absorption onset and show a good visible light absorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] This unique single-domain-single-grain polycrystalline structure can be used for a mechanistic study of polycrystalline BiFeO 3 film in multifunctional applications without a domain wall contribution. [23] Figure 5a shows the UV-vis spectra of the three thin films with Figure 5b showing the derived Tauc-plots. From the absorption spectra, it can be seen that the BiFeO 3 thin films annealed in different atmospheres have a very close light absorption onset and show a good visible light absorption.…”
Section: Resultsmentioning
confidence: 99%
“…[ 22 ] This unique single‐domain‐single‐grain polycrystalline structure can be used for a mechanistic study of polycrystalline BiFeO 3 film in multifunctional applications without a domain wall contribution. [ 23 ]…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there is no necessity for domain wall formation to minimize the internal stresses which are already reduced as the Ps is decreased. 66,67 Fig. 4b shows a TEM image of the WC/RbBi2Ti2NbO10 nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that Ba 0.8 Sr 0.2 TiO 3 with polar domain has a faster reaction rate (k = 0.18 min À 1 ) than Ba 0.2 Sr 0.8 TiO 3 with the nonpolar one (k = 0.11 min À 1 ), which disclosed that enhanced photoactivity of Ba 0.8 Sr 0.2 TiO 3 stems from the inherent polarization of the domain instead of domain walls. [47] Annealing treatment can improve the crystallinity to enhance ferroelectricity of ferroelectric semiconductors. The content of tetragonal phase of BaTiO 3 powder can be increased by annealing treatment under 1200 °C, which increased ferroelectricity than predominantly cubic BaTiO 3 .…”
Section: Chemistry-a European Journalmentioning
confidence: 99%